Engineering electrocatalytic activity in nanosized perovskite cobaltite through surface spin-state transition - Shiming Zhou (Nature Portfolio, 2016)
The activity of electrocatalysts exhibits a strong dependence on their electronic structures. Here, the authors manipulate the eg filling of perovskite cobaltite LaCoO3nanoparticles by changing particle size and show improved oxygen evolution activity with increased numbers of surface high-spin cobalt ions.